Role of zirconium in neodymium-dopants interactions within uranium-based metallic fuels. (March 2021) - Khanal, Rabi; Ayers, Nicholas; Jerred, Nathan; Benson, Michael T.; Mariani, Robert D.; Charit, Indrajit; Choudhury, Samrat
Abstract: Metallic fuels proposed for advanced nuclear reactors are found to be superior to other fuel types in terms of high thermal conductivity, proliferation resistance, excellent compatibility with the sodium coolant, and in some configurations inherent safety. One performance limitation of metallic fuel systems is the chemical interaction of fuel, and the surrounding cladding materials commonly, known as fuel-cladding-chemical interaction (FCCI). The use of dopants that form intermetallics with lanthanides within the fuel matrix was found to be effective in binding with FCCI-causing lanthanides and arresting them within the fuel matrix. While most computational studies till now have been focused on the interaction between dopant and lanthanide, in this article we focused on the role of Zr, the primary solute in the U–Zr system on the complex phase stability in U–Zr–Nd–X quaternary system, where Nd and X=As, Se, Pd, Te, Sb are the lanthanide and dopants, respectively. We present combined electronic structure calculations and experiments to systematically understand the multiple binary interactions between dopant (X), lanthanide (Nd), and Zr within the U matrix. Our result reveals that while Zr–dopant interaction helps to stabilize dopants in the ternary U–Zr–dopant alloys system, dopant-lanthanide interaction is more dominant than any other binary interaction within the quaternary U–Zr–Nd–X system, implying the dopants are still effective in arresting lanthanide within the U matrix, in the presence of Zr providing further impetus for the use of dopants. Highlights: Fuel-cladding-chemical interaction (FCCI). Electronic structure guided alloy design. Role of zirconium in dopant-lanthanide interactions.